Political embeddedness and firms' choices of earnings management strategies in China. (17th August 2020) - Wang, Zhi; Braam, Geert; Reimsbach, Daniel; Wang, Jiaxin
Abstract: We examine whether and how political embeddedness influences financial reporting quality in China by investigating how government ownership and political connections affect Chinese listed firms' choices of earnings management strategies. The results show that state‐owned enterprises (SOEs), and in particular, central SOEs, are more likely to substitute accrual‐based earnings management strategies with costlier but less detectable real earnings management strategies than non‐SOEs. The results also indicate that politically connected enterprises (PCEs) are more likely to employ less detectable real earnings management strategies than non‐PCEs, so much so that PCEs' total earnings management level is higher than that of non‐PCEs.